The association between vitamin D level and periodontal disease in Saudi population, a preliminary study - Marwa Madi; Verica Pavlic; Shahad Mongith Alammar; Leenah Mohammad Alsulaimi; Reema Shaker Alotaibi; Gadah Mohammed AlOtaibi; Osama Zakaria (Saudi Dental Journal)
Objective: Among other regulatory functions, vitamin D has a role in modulating the inflammatory process of periodontal disease. Therefore, this retrospective study aimed to assess the relationship between vitamin D levels and periodontal health in dental patients from the Eastern Province of Saudi Arabia. Methods: Radiographs and serum vitamin D levels of patients seeking dental treatment were collected. Exclusion criteria were systemic disease, smoking, recent vitamin D supplementation, and previous periodontal surgery. Gender, age, and alveolar crest height (ACH) were recorded. A total of 67 patients were categorized into three groups according to their serum vitamin D level (<10, <20, and > 20 ng/mL) and their bone loss compared. Results: Differences in means were compared by t-test. ANOVA was used to compare vitamin D groups and the corresponding ACH, as well as the correlation (p < .05). Patients with vitamin D levels > 20 ng/mL demonstrated a mean ACH of 1.6 mm. The mean ACH was 3.1 mm for those with vitamin D levels < 20 ng/mL, and 4.6 mm for vitamin D levels < 10 ng/mL. A weak negative correlation was found between vitamin D and ACH in all groups (r = −0.055, p = .7). Conclusion: Serum vitamin D level seems to be an important factor that influences oral health, especially the periodontal condition, of both male and female patients.